The role of endometrial sampling for surveillance of recurrence in postmenopausal patients with medically inoperable stage I endometrial cancer - Angelina Carey-Love; Mary M. Mullen; Abigail Zamorano; Stephanie Markovina; Andrea R. Hagemann; Katherine C. Fuh; Premal H. Thaker; David G. Mutch; Matthew A. Powell; Lindsay M. Kuroki (Elsevier, 2021)
It is unclear if surveillance for postmenopausal women with medically inoperable stage 1 endometrial cancer (EC) should differ depending on their management strategy. Thus, we investigated the utility of surveillance endometrial sampling among 53 postmenopausal women with medically inoperable, clinical stage I, grade 1 endometrioid EC who received either progestin therapy or radiation between 2009 and 2018, at a single academic institution. Frequency and results of endometrial sampling, as well as recurrence and survival rates were studied. Of 53 patients, 18 (34.0%) received progestin therapy and 35 (66.0%) radiation. Medically managed patients were treated with megestrol acetate (27.7%), a levonorgestrel intrauterine device (27.7%), or both (44.4%). Radiated patients were mostly treated with high-dose rate brachytherapy only (77.1%). Surveillance endometrial sampling (median procedures = 4, range 1-10) was strictly adhered to among all patients who received progestin therapy, but infrequently (6/35, 17.1%) performed among radiated patients, yielding no positive results. Three recurrences occurred over the median follow-up of 38 months. Two (11%) women in the progestin therapy group recurred locally and were diagnosed by endometrial sampling. One (3%) patient in the radiation group recurred distally in the lung 25.3 months after completing brachytherapy. We conclude that appropriate surveillance for women with medically inoperable, clinical stage I, grade 1 EC depends on the management strategy. For those treated with progestins, surveillance with endometrial sampling every 3-6 months can reveal local recurrence. However, given the excellent local control after radiation, endometrial sampling may not be warranted for women treated with definitive radiation.